Applications of Freudian Psychoanalysis in Rebecca - Christine Resnitriwati Respatio (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
AbstractPeople’s soul is a mistery and is difficult to be understood. This is because our consious life just only appears in small portion (1/8 part) meanwhile most of them (7/8 part) can not be seen. In our unconcious lif, thre are lots of needs that must be fullfilled and people find out the way by themselves to do that, for examples by writing, painting and even by dreaming. The purpose of this paper is to analyze the dreams and halucinations the main character has in Rebecca. The writer used Freud’s psichoanalysis to analyze the main character’s dreams and hallucinations. The results show that the young woman as the main character in Rebecca is able to overcome her bad dreams and hallucinations. She grows being a strong mature woman.Key words: id, ego, superego, hallucinations, psychoanalysis